Comparação entre protocolos de estimulação transcraniana por corrente contínua em mulheres com migrânea crônica: ensaio clínico, triplo-cego, placebo-controlado - Aranha, Renata Emanuela Lyra de Brito (2018)
The symptomatic picture of chronic migraine is quite broad with debilitating consequences and cognitive dysfunctions that impact the quality of life of the individual. In this context, transcranial Direct Current Stimulation (tDCS) may be an adjunct to drug treatment, requiring a better standardization and definition of its application protocols. Objective: To analyze if the clinical and cognitive effects of tDCS, observed in patients with chronic migraine, vary according to the number and interval between sessions. Method: This study consisted of a triple-blind, randomized, placebo-controlled trial. The sample consisted of women aged between 20 and 45 years with diagnosis of chronic migraine. A sociodemographic, clinical questionnaire and the following outcomes were used: Headache Impact Test (HIT-6), Cumulative Illness Rating Scale (CIRS), Beck Depression Inventory (BDI), Trait-State Anxiety Inventory (IDATE), Montreal Cognitive Assessment, Wechsler Adult Intelligence Scale (WAIS-III), Hayling's Test, Letter Comparison and Pattern Comparison, Nine Hole Peg Test, D2 Test, Visual Attention Test, Trail Making Test Part B . The subjects enrolled in the study were randomly assigned to 3 groups: Group A: received a single session of tDCS for 15 minutes (protocol 1); Group B: received two 15-minutes sessions with an interval of 20 minutes between them (protocol 2); Group C: received sham current for 15 minutes. The anodic electrode was allocated over the left dorsolateral prefrontal cortex region (DLPFC) and the reference electrode in the contralateral supraorbital region. The current had intensity of 2mA and was applied during 10 consecutive days, excluding the weekends. Results: We observed that anodic tDCS reduced the inability of migraine, stress level and cognitive decline. We also found an improvement in working memory and attention, executive functions, motor processing speed, and selective attention. However, the effects of tDCS on group B were not superior to group A and more adverse effects were reported. Conclusion: tDCS is a safe and effective adjuvant technique in patients with chronic migraine, but further studies are needed to standardize the protocol that is most appropriate for this population.